Distribution and metabolism of daidzein and its benzene sulfonates in vivo (in mice) based on MALDI-TOF MSI - Jiao, Yanxiao; Li, Xueqin; Tang, Yao; Peng, You; Chen, Guisen; Wang, Xin; Yan, Long; Liu, Huihui; Nie, Zongxiu (Frontiers in Pharmacology, 2022)
Daidzein (D1) has been proved to be of great benefit to human health. More and more attention was paid to the metabolic process of D1. Most studies focused on the metabolites of D1 and analogues were determined through excretion of animals and humans by traditional HPLC-MS, while their in situ distribution and metabolism in organs in vivo has not been reported. In our group, novel daidzein sulfonate derivatives were synthesized and confirmed to have excellent pharmaceutical properties. They exhibited good anti-inflammatory, inhibitory activities on human vascular smooth muscle cells (HVSMC) proliferation and other bioactivities. Compared with traditional analytical methods, matrix assisted laser desorption ionization time-of-flight mass spectrometry imaging (MALDI-TOF MSI) can directly analyze the distribution of compounds in tissues and organs. In this study, we investigate in situ the distribution and metabolism of D1 and its derivatives (DD2, DD3) in organs of mice based on MALDI-TOF MSI for the first time. Trace prototype compounds were detected in the plasma 4 h after the intravenous injection of D1, DD2 and DD3. Seven phase I metabolites and seven phase II metabolites were detected. D1 sulfates were found in plasma and organs except heart. The presence of D1 and DD3 monosulfate in brain indicated that they could penetrate the blood-brain barrier. DD2 and DD3 could be hydrolyzed into D1 and their metabolic pathways were similar to those of D1. In addition, ligand-receptor docking of D1 and DD2 with mitogen-activated protein kinase 8 (JNK1) was performed because of their significant anti-inflammatory activities through JNK signaling pathway. It showed that the binding energy of DD2 with JNK1 was obviously lower than that of D1 which was consistent with their anti-inflammatory activities. It provided a theoretical basis for further validation of their anti-inflammatory mechanism at the protein level. In summary, the research will provide beneficial guidance for further pharmacological, toxicological studies and clinical use research of these compounds.